'Are We Worth Saving? You Tell Me': Neoliberalism, Zombies and the Failure of Free Trade. Issue 2 (1st November 2015) - Unknown
Abstract : The popular cultural ubiquity of the zombie in the years following the Second World War is testament to that monster' s remarkable ability to adapt to the social anxieties of the age. From the red-scare zombie-vampire hybrids of I Am Legend (1954) onwards, the abject alterity of the ambulant dead has been deployed as a means of interrogating everything from the war in Vietnam ( Night of the Living Dead, 1968) to the evils of consumerism ( Dawn of the Dead, 1978). This essay explores how, in the years since 9/11, those questions of ethnicity and gender, regionality and power that have haunted the zombie narrative since 1968 have come to articulate the social and cultural dislocations wrought by free-market economics and the' shock doctrines' that underscore the will to global corporatism. The article examines these dynamics through consideration of the figure of the zombie in a range of contemporary cultural texts drawn from film, television, graphicfi ction, literature and gaming, each of which articulates a sense not only neo-liberalism itself has failed but simply won't lie down and die. It is therefore argued that in an age of corporate war and economic collapse, community breakdown and state-sanctioned torture, the zombie apocalypse both realises and works through the failure of the free market, its victims shuffling through the ruins, avatars of the contemporary global self.